Ableist realism and inclusive education: theorising the cultural and atmospheric dimensions - Vaahtera, Touko; Kauppila, Aarno; Niemi, Anna-Maija; Mietola, Reetta (Informa UK Limited, Trading as Taylor & Francis Group, 2026)
Invoking realism is one of the overlooked forms of ableism in the discussions of disability studies and inclusive education. By introducing the concept of ableist realism, the aim of the article is to show how such forms of ableism could be theorised. Authors understand ableist realism to be a mentality and an atmosphere, where understanding disability as a deficiency and considering disabled people’s needs inappropriate to general societal settings are evoked as part of an inescapable reality. From the perspectives of cultural studies and by drawing on qualitative research authors re-examine their existing data from their earlier projects in various educational settings. The datasets include expert interviews and life-historical interviews with young people. The authors first explore how special education experts use the idea of realism when considering inclusive education. After that they turn to the accounts of young people who have received special education, explore their accounts about career guidance, and consider what perspectives the idea of atmosphere brings to the exploration of ableist realism.